Корпорация как источник формирования корпоративной среды (Путеводитель предпринимателя, 2020)
In article formation of the corporate environment is considered, "corporation" is spent the analysis of the given process, proceeding from genesis of the concept, and on this basis definition of the corporate environment as specific, characteristic for the given organization of system of communications, actions, relations and mutual relations which are carried out within the limits of concrete enterprise activity, спроецированной on the local, regional, national or international market is made.